2009
DOI: 10.1128/mcb.01047-08
|View full text |Cite
|
Sign up to set email alerts
|

Human UBN1 Is an Ortholog of Yeast Hpc2p and Has an Essential Role in the HIRA/ASF1a Chromatin-Remodeling Pathway in Senescent Cells

Abstract: Cellular senescence is an irreversible proliferation arrest, tumor suppression process and likely contributor to tissue aging. Senescence is often characterized by domains of facultative heterochromatin, called senescenceassociated heterochromatin foci (SAHF), which repress expression of proliferation-promoting genes. Given its likely contribution to tumor suppression and tissue aging, it is essential to identify all components of the SAHF assembly pathway. Formation of SAHF in human cells is driven by a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
177
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(189 citation statements)
references
References 73 publications
12
177
0
Order By: Relevance
“…To determine which subunit interacted with OGT, we first used HIRA mutants to define the OGT-HIRA proteinprotein interaction domain in vivo. HIRA contains three domains: the HIRA A region (residues 1-400) that consists of WD40 repeats and interacts with the N terminus of UBN1 (49,50); the HIRA B domain (residues 401-500) that interacts with ASF1a (33, 51, 52); and the HIRA C domain (residues 501-1017) that binds CABIN1 (28) (Fig. 1D, Top).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine which subunit interacted with OGT, we first used HIRA mutants to define the OGT-HIRA proteinprotein interaction domain in vivo. HIRA contains three domains: the HIRA A region (residues 1-400) that consists of WD40 repeats and interacts with the N terminus of UBN1 (49,50); the HIRA B domain (residues 401-500) that interacts with ASF1a (33, 51, 52); and the HIRA C domain (residues 501-1017) that binds CABIN1 (28) (Fig. 1D, Top).…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that O-GlcNAc modification of HIRA influences the expression of the HIRA complex. However, unlike depletion of HIRA complex subunits that affects the stability of other subunits (28,49), depletion of OGT does not affect the expression of three HIRA subunits (Fig. 3 A and B).…”
Section: Discussionmentioning
confidence: 99%
“…HIRA has two orthologs in Saccharomyces cerevisiae, Hir1p and Hir2p, and biochemical purification of the Hir complex in this species revealed the presence of two co-purifying proteins Hir3 and Hpc2. Interestingly, their corresponding orthologs in human, Cabin1 and Ubinuclein (UBN1 and 2), respectively [63,64], co-purify with human H3.3 in a sub-complex with HIRA, showing that the yeast Hir complex is conserved in human [57,65]. It is thus tempting to speculate that HIRA is likely to function as a complex in the process of H3.3 deposition although the respective role of each protein is still unclear.…”
Section: Hira Complexmentioning
confidence: 99%
“…In addition, it was shown that knockdown of Asf1a by RNAi impairs OIS induced by overexpression of H--RasV12 (Zhang et al 2005). other members of the HIRA complex, namely UBN1 and Cabin1 were also shown to localize to PML--NBs only in senescent cells, and ectopic expression of these two proteins also led to SAHF formation and senescence entry, suggesting a function of the entire HIRA histone chaperone complex in SAHF assembly (Banumathy et al 2009;). Thus, these data suggested that the H3.3 histone chaperones forming the HIRA complex localize to PML--NBs during senescence and that this is important for SAHF formation (Fig.…”
Section: Role Of Histone Chaperones and How They Are Linked To Pml Numentioning
confidence: 99%